Rhipicephalus sanguineus salivary gland extract as a source of immunomodulatory molecules - Pereira, Melissa Carolina [UNESP]; Nodari, Elen Fernanda [UNESP]; de Abreu, Marina Rodrigues [UNESP]; Paiatto, Lisiery Negrini; Simioni, Patrícia Ucelli; Camargo-Mathias, Maria Izabel [UNESP] (Springer Nature, 2021)
Rhipicephalus sanguineus sensu lato (s.l.), popularly known as ‘brown dog tick’, is the primary vector of pathogens affecting dogs worldwide. To enter the host’s organism, these pathogens utilise the anticoagulant, antiplatelet, anti-inflammatory and immunomodulatory actions of compounds present in the tick’s saliva; such compounds are released by the ectoparasite in order to attach and feed on dogs. Nitric oxide (NO) is one of the regulatory factors in inflammation, apoptosis and immunomodulation. Here, we evaluated the in vitro activity of salivary gland extract of female dog ticks on the macrophage-derived J774 cell line, with and without lipopolysaccharide (LPS) stimulation. Cultures were evaluated for possible morphological alterations caused by exposure to the extract. There was no apparent in vitro cytotoxicity of the extract. Also, the NO secretory response in the non-LPS-stimulated cells was not inhibited. On the other hand, the extract presented modulatory action in the cultures of LPS-stimulated cells at a concentration of 0.1 μg/mL, possibly through macrophage activation, and induced a significant decrease in NO secretion. These results confirm the modulatory potential of bioactive molecules in the salivary glands of R. sanguineus ticks.
Keywords: Ectoparasite-host relationships; Nitric oxide; Saliva; Ticks